2010
DOI: 10.1073/pnas.1003480107
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin-dependent neuron–neuron interaction is required for the maintenance of activity-induced dendrite growth

Abstract: Formation of neural circuits depends on stable contacts between neuronal processes, mediated by interaction of cell adhesion molecules, including N-cadherin. In the present study, we found that activity-dependent dendrite arborization specifically requires Ncadherin-mediated extracellular neuron-neuron interaction, because the enhancement did not occur for neurons cultured in isolation or plated on an astrocyte monolayer and was abolished by a recombinant soluble N-cadherin ectodomain. Furthermore, depolarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 40 publications
(43 reference statements)
5
76
0
1
Order By: Relevance
“…High-density mixed neuronal-glial cultures were prepared from SpragueDawley rat pups on postnatal day 0 (P0) as previously described [49,50]. Briefly, hippocampi, with the dentate gyri removed, were dissected, and dissociated neurons were plated on glass coverslips (63- For dentate granule cell cultures, only the dentate gyrus was cultured, and Prox 1 immunostaining was used to confirm the identity of the granule cells.…”
Section: Hippocampal Neuronal Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…High-density mixed neuronal-glial cultures were prepared from SpragueDawley rat pups on postnatal day 0 (P0) as previously described [49,50]. Briefly, hippocampi, with the dentate gyri removed, were dissected, and dissociated neurons were plated on glass coverslips (63- For dentate granule cell cultures, only the dentate gyrus was cultured, and Prox 1 immunostaining was used to confirm the identity of the granule cells.…”
Section: Hippocampal Neuronal Culturesmentioning
confidence: 99%
“…The lateral ventricles of E15.5 embryos were injected with 2 lL Qiagen Maxiprep DNA and Fast Green dye using a pulled micropipette. The following plasmids were used: pCMV-LifeAct-TagRFP [51] (3 lg/lL; 60102, ibidi GmbH, Martinsried, Germany), GFP-actinin [52] (3 lg/lL), tdTomato [53] (0.5 lg/lL; 22478, Addgene, Cambridge, MA; originally named FUtdTW), and pCS2 min-GFP [49] (1 lg/lL). Forceps-type electrode paddles controlled by an ECM 830 electroporator (BTX Instrument Division, Harvard Apparatus Inc, Holliston, MA) were used to deliver 5 pulses at 60 mV with 50 ms duration at 100 ms intervals.…”
Section: In Utero Electroporationmentioning
confidence: 99%
“…Because our data showed that CRP1 is required for dendritic growth in neurons, we hypothesized that CRP1 may act as a mediator for dendritic growth induced by Ca 2ϩ influx. It has been reported that when neurons were depolarized with KCl at 3 DIV, enhanced dendritic growth is observed in both cortical neurons and hippocampal neurons (Redmond et al, 2002;Tan et al, 2010). We first measured CRP1 expression in cultured hippocampal neurons after depolarization using the same condition as reported previously (Redmond et al, 2002).…”
Section: Crp1 Is Upregulated By Camentioning
confidence: 99%
“…The 488-kb gain in CN encompasses CDH2, encoding N-cadherin, which is expressed in brain, skeletal and cardiac muscles and has critical roles in synaptic adhesion, dendritic morphology and neuritic growth. [55][56][57][58][59] CDH2 has been extensively studied in AD. For example, inhibition of N-cadherin function has been reported to accelerate Ab-triggered synapse damage.…”
Section: Rare Autosomal Cnvs In Eo-fad Bv Hooli Et Almentioning
confidence: 99%